SOCIOMETRIC METHODS IN THECHNOLOGICAL AND INFORMATION TECHNOLOGY EDUCATION - Henryk, NOGA (Trends in education, 2009)
Pedagogical research conducted by a teacher always aims at an exact problem chosen in advance. It is carried out either once - to learn something more about a given phenomenon, or periodically - to find out what changes occur in a particular group of students. The knowledge obtained by means of various research methods and techniques helps to control a given class better, it allows to reinforce positive changes and to suppress negative ones.Research methods and techniques in pedagogy are divided into quantitative and qualitative ones. Quantitative methods are usually based on descriptions and statistical conclusions. Qualitative methods are based on interpretation and the understanding of the sense and meaning of individual evidence. The following article shows how to use the sociometric methods in technical and information technology education.
Keywords: sociometric methods; pedagogical research; technical and information technology education